RANCANGAN BUKU PENYUSUNAN SOAL UJIAN SEKOLAH BERSTANDAR NASIONAL (USBN) MATA PELAJARAN BIOLOGI BAGI GURU SMA - Yennisa, Dea; Natalina L, Mariani; Suryawati, Evi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research aims to produce a book on the preparation of national standardized school examination questions (USBN) for biology subjects for high school teachers of good quality. The research consists of analyze stage, design stage, and development stage. The stage of analyze, design, development, internal validation and limited trial phase I was carried out in the Biology Education Laboratory FKIP University of Riau. External validation was carried out in SMA Negeri 8 Pekanbaru and SMA Negeri 1 Pekanbaru. The limited trial phase II was carried out in SMA/MA Kota Pekanbaru. The book is validated based on four indicators, namely: book format and graphics, illustrations and pictures, language, and content eligibility. The overall results of the validation obtained an average of 3,46 with very valid categories. The results of the limited trial phase I have an average of 3,61 with very good categories and the results of the limited trial phase II have an average of 3,63 with very good categories.The book produced in this study has a very valid and very good categories so that it is worthy of being used as a source of teacher learning in developing assessment skills, especially the preparation of questions.Key Words: USBN Books, senior high school teachers, biology subjects